A Reflection of Cautiousness in the Lexicon “Fall” in Sundanese: An Ethnosemantic Study - Intan Kusuma Wulandari (Humanitatis : Journal of Language and Literature, 2023)
In Sundanese, there are various terms "fall" which have different functions and can be represented by the 'falling sound’ or the 'visualization'. This research uses a descriptive qualitative research method. The ethnosemantics study explains how the reflection of the Sundanese concept on paying attention to cautiousness in everyday life. Based on its usage, the term "falling" can be categorized for animate or inanimate. This article focuses on how "falls" are defined by its function and how "falls" be the reflection of cautiousness, also this article discusses the various types of falling lexicon based on: (i) falling objects downwards; (ii) falling objects based on the object's position and direction; (iii) falling on a slippery surface; (iv) falling due to an object; and (v) the object falls so that it shifts its place. The phrase ragrag jabatan 'fall from the job position' is an example of how the lexicon "falls" becomes a perspective on how everyone must maintain an attitude in carrying out work. This research explains the function of affixation in each lexicon that builds its meaning and explains the values of cautiousness and vigilance in carrying out daily life in all its activities.